Modulation of the NOP receptor signaling affects resilience to acute stress. (December 2019) - Holanda, Victor A D; Pacifico, Salvatore; Azevedo Neto, Joaquim; Finetti, Luca; Lobão-Soares, Bruno; Calo, Girolamo; Gavioli, Elaine C; Ruzza, Chiara
Background: The peptide nociceptin/orphanin FQ (N/OFQ) and its receptor (NOP) are implicated in the modulation of emotional states. Previous human and rodent findings support NOP antagonists as antidepressants. However, the role played by the N/OFQ–NOP receptor system in resilience to stress is unclear. Aims: The present study investigated the effects of activation or blockade of NOP receptor signaling before exposure to acute stress. Methods: The behavioral effects of the administration before stress of the NOP agonists Ro 65-6570 (0.01–1 mg/kg) and MCOPPB (0.1–10 mg/kg), and the NOP antagonist SB-612111 (1–10 mg/kg) were assessed in mice exposed to inescapable electric footshock and forced swim as stressors. The behavioral phenotype of mice lacking the NOP receptor (NOP(-/-)) exposed to inescapable electric footshock was also investigated. Results: The activation of NOP receptor signaling with the agonists increased the percentage of mice developing helpless behavior and facilitated immobile posture. In contrast, the blockade of NOP receptor reduced the acquisition of depressive-like phenotypes, and similar resistance to develop helpless behaviors was observed in NOP(-/-) mice. Under the same stressful conditions, the antidepressant nortriptyline (20 mg/kg) did not change the acquisition of helpless behavior and immobile posture. Conclusions: These findings support the view that NOP activation during acute stress facilitates the development of depressive-related behaviors, whereas NOP blockade has a protective outcome. This study showed for first time that NOP antagonists are worthy of investigation as preemptive treatments in patients with severe risk factors for depression.